Income and the (eventual) rise of democracy - Dario Debowicz (Public Choice, 2025)
We investigate the relationship between income and democracy. A theoretical framework is developed where citizens derive utility from both material goods and political rights. Citizens can devote their time either to creating material benefits or to political activism (that improves political liberties). We demonstrate a non-monotonic relationship between income and democracy. In low income countries—where the elasticity of the marginal rate of substitution between material goods and political rights is low because of small incomes—exogenous increases in income (wages) lead to a reduction in the level of political liberties: as wages increase, citizens are increasingly willing to give up time otherwise devoted to activism to work more. In high income countries, the opposite is true: political liberties increase with income. Our country fixed-effects and GMM estimations on cross-country data over 1960–2010 empirically validate this non-monotonic prediction, thereby corroborating our theory above-and-beyond the effect of institutions and culture. The predictions are equally validated for data spanning back to 1800.